Emergence of K1 ST23 and K2 ST65 hypervirulent klebsiella pneumoniae as true pathogens with specific virulence genes in cryptogenic pyogenic liver abscesses Shiraz Iran - Sohrabi, Maryam; Alizade Naini, Mahvash; Rasekhi, Alireza; Oloomi, Mana; Moradhaseli, Farzad; Ayoub, Abbas; Bazargani, Abdollah; Hashemizadeh, Zahra; Shahcheraghi, Fereshteh; Badmasti, Farzad (Frontiers in Cellular and Infection Microbiology, 2022)
Hypervirulent Klebsiella pneumoniae (hvKp) pathotype is emerging worldwide in pyogenic liver abscesses (PLAs). However, the role of virulence factors in pathogenicity remains unclear. On the other hand, the epidemiology of PLAs in Iran is unknown. From July 2020 to April 2022, bacterial species were isolated and identified from the drainage samples of 54 patients with PLAs. K. pneumoniae as the most common pathogen of pyogenic liver abscesses was identified in 20 (37%) of the 54 patients. We analyzed the clinical and microbiological characteristics of K. pneumoniae-related pyogenic liver abscesses. Antibiotic susceptibility testes and string test were performed. 16S rRNA, antibiotic resistance, and virulence genes were determined by polymerase chain reaction amplification. Clonal relatedness of isolates was identified by multilocus sequence typing. Virulence levels were assessed in the Galleria mellonella larval infection model. Four hvKp isolates (K1/K2) were found to be responsible for cryptogenic PLAs, and 16 classical K. pneumoniae isolates (non-K1/K2) were associated with non-cryptogenic PLAs. Three capsular serotype K1 strains belonged to sequence type 23 (ST23) and one K2 strain to ST65. Meanwhile, the non-K1/K2 strains belonged to other STs. ST231 was the most common strain among the classical K. pneumoniae strains. Compared with the non-K1/K2 strains, capsular serotypes K1/K2 strains were less resistant to antibiotics, had positive string test results, and had more virulence genes. In Galleria mellonella, a concentration of 106 colony-forming units of the K1 hvKp strain resulted in 100% death at 24 hours, confirming the higher virulence of the hvKp strain compared with cKp. K. pneumoniae isolates represented that the acquisition of any plasmid or chromosomal virulence genes contributes to pathogenicity and high prevalence in PLAs. Meanwhile, hvKp isolates with a specific genetic background were detected in cryptogenic PLAs.